Study on Convergent Pooling Technology Strategy with SGSN and MME - Jie Miao; Gongying Gao; Jia Mu (Dianxin kexue)
Based on 3GPP evolution background and pooling technology of 3GPP convergent core network analysis, technical challenges and the corresponding solutions were discussed, including the network coverage planning and network identity mapping schemes, and the comparison between schemes was conducted, finally suggestions were given on the network convergent pooling strategy for the present network deployment.